Diseño y desarrollo de un instrumento de medición de presión diferencial para perfiles aerodinámicos en vehículos de competencia (2017)
"In Colombia, more specifically in the environs in Bogota, the automotive development of track sports has been taking place since the beginning of the 70s with the opening of the first Autodrome in this area commonly known as Ricardo Mejía, which changed management giving a phase development and implementation of works in order to create advances in merchandising and marketing of sports activity, always with the endorsement of international authorities expert in the subject... At the University of the Andes, efforts were concentrated on the flat bottom of the vehicle, specifically on the front (in the diffuser), therefore, this document describes the methodology of the design and development of a sensor rack to measure the Differential pressure in a race sports vehicle during a race." -- Tomado del Formato de Documento de Grado.